Space flight dynamics - Kluever, Craig A. (John Wiley & Sons, Inc., 2018)
With practical, real-world examples illustrating key concepts throughout, this concise resource provides thorough coverage of space flight topics with self-contained chapters serving a variety of courses in orbital mechanics, spacecraft dynamics, and astronautics. -- Edited summary from book.
Keywords: Astrodynamics.; Space flight.; Space flights.; elektronické knihy; electronic books